2015
DOI: 10.1002/acp.3139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interest, Thematic Congruence, and Typicality on Memory for Television, Radio, and Press Advertisements of New Products

Abstract: Little is known about how the content of advertisements is remembered. We studied how product interest, thematic congruence between advertisement and programme, and the typicality of the elements of an advertisement affect memory for new product ads in television, radio, and printed media. Participants were exposed to a single type of media with two embedded ads. After a filler task, they completed a true/false recognition task. In television and radio, accuracy was higher for the interesting product ads. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Previous research by Moore et al (2005) has shown that congruity has a positive effect on consumer attitudes. Positive effect of congruity is also supported by recent research across different domains (Furnham and Goh, 2014; Martín-Luengo et al , 2015; Janssens et al , 2012). Similar results were found by Kamins et al (1991) and Bendall-Lyon and Powers (2004) who state that the effect of mood congruence between ads and TV programs result in more favorable evaluations.…”
Section: Conceptual Framework and Hypothesis Developmentsupporting
confidence: 65%
“…Previous research by Moore et al (2005) has shown that congruity has a positive effect on consumer attitudes. Positive effect of congruity is also supported by recent research across different domains (Furnham and Goh, 2014; Martín-Luengo et al , 2015; Janssens et al , 2012). Similar results were found by Kamins et al (1991) and Bendall-Lyon and Powers (2004) who state that the effect of mood congruence between ads and TV programs result in more favorable evaluations.…”
Section: Conceptual Framework and Hypothesis Developmentsupporting
confidence: 65%
“…Ads embedded in a highly appreciated TV context resulted in a more positive attitude toward the ad; ad content was also positively impacted by positively regarded media content. Advertisers generally tend to choose media content that is related thematically to their product (MartinLuengo, Luna, and Migueles, 2015). However, research does not unequivocally confirm that choosing thematically congruent content allows for more effective advertising.…”
Section: Advertising Context and Ad Programming Congruencementioning
confidence: 93%
“…On the contrary, Furnham, Gunter, and Richardson (2002) find better recall for ads embedded in an incongruent context. There is no explicit answer as to whether thema tic congruence affects ad recall as most of the studies are either inconclusive or identify no differences (MartinLuengo, Luna, and Migueles, 2015).…”
Section: Advertising Context and Ad Programming Congruencementioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, consumers view incoming information about a given product in light of existing knowledge and associations, such as characteristics of the product category, retailer, or brand image (Banerjee & Drollinger, 2017; Lee & Choi, 2019). A high typicality element is a basic feature that defines a product and used to improve the memory of advertising (Martín‐Luengo et al, 2015). It can lead to a positive attitude toward advertising, sponsorship, and purchase intention (McDaniel, 1999).…”
Section: Introductionmentioning
confidence: 99%